A Survey on Information Diffusion Models in Social Networks - Singh, Shashank Sheshar; Singh, Kuldeep; Kumar, Ajay; Shakya, Harish Kumar; Biswas, Bhaskar (Advanced Informatics for Computing Research, 2018)
Nowadays, social influence plays an important role in everyday life because peoples are spending too much time in social the networks. Social influence is the change in a people behaviors, thoughts, attitudes, and feeling by interacting other peoples in the social networks. Thus, analysis of social influence spreading has emerged as an important topic of interest in areas of computer science, economics, and sociology. In 1940s, only empirical studies of diffusion process have been done. In 1970s, some theoretical propagation models were proposed. Later, motivated by marketing strategy influence maximization problem is emerges. The main objective of influence maximization (IM) problem is to maximize the social influence spreading with fixed predetermined budget k in online social networks such as twitter, Epinions, Facebook, HEP-PH and Google+ etc.